Vapor Pressure and Boiling Point Elevation of Eucalyptus Kraft Black Liquors - Ferreira,Abel (2011)
Vapor-liquid equilibria and boiling point elevation of eucalyptus kraft black liquors over a wide range of solid concentrations (up to 72% solids) has been studied. The liquors were prepared from original samples taken from the outlet of the evaporation plant of a Portuguese mill. It was found that boiling point elevation of black liquors is pressure and temperature dependent and this dependency is more significant at higher solids concentrations. The heat of vaporization is not strongly affected by solids content. The boiling point elevation data at different solids contents (at a fixed pressure) were correlated with the dissolved solids in black liquor. We have observed a change in the slope of the boiling point elevation as a function of the dissolved solids at nearly 43% solids.